Analysis of Islamic Legal Anthropology on The Marriage Traditions of The Mbojo and Samawa Tribes: (A Comparative Study of the Peta Kapanca and Barodak Rapacar Traditions) - Rizki, Prasetio; Wardatun, Atun; Mutawali, Muhammad (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
This research aims to describe the similarities and differences in the traditional marriages of the Mbojo and Samawa tribes, as well as how Islamic legal anthropology analyzes these aspects. The study employs qualitative research through field research methods. A qualitative approach is used to observe and convey information that will produce clear data, based on community activities regarding how they are subjects within the research object. This research also contains comparative elements, which involve comparing two situations, events, and occurrences. In this case, the researcher applies a comparative method to the traditional marriages of the Mbojo tribe (Bima) and the Samawa tribe (Sumbawa). Data collection techniques in this study are obtained through direct observation in the field and interviews. Additionally, the data used in this research is supported by literature sources such as books, theses, journals, internet media, and others that support the research. The results of this study indicate that one of the purposes of marriage is to create a family that is peaceful, secure, and harmonious, in line with the concept of sakinah mawaddah wa rahmah. Marriage is a sacred bond between a man and a woman. In anthropology, culture is a system of ideas, actions, and human works that encompass beliefs, arts, morals, laws, and customs. In Indonesia, each region has its own unique culture, including in wedding ceremonies, such as those of the Mbojo tribe in Bima and the Samawa tribe in Sumbawa. Although they have different names and processes, the traditions of peta kapanca and barodak rapacar share the same purpose: to purify oneself in order to achieve a good and harmonious household.